Rekonsiliasi Melalui Pembaruan Misi PL dan Pengaruh Sosial Kisah Para Rasul 15 dalam Ekklesia Multikultural - Anon Dwi Saputro; Daniel Lindung Adiatma (LOGON ZOES: Jurnal Teologi, Sosial dan Budaya, 2024)
This research aims to investigate the role of renewing mission based on the Old Testament in the process of reconciliation within the context of multicultural ecclesia. The primary focus of this research is on the narrative of Acts 15, which provides a framework for understanding how the renewing mission of the Old Testament can be adapted to achieve reconciliation among diverse communities. The author will employ a literature-based approach in exploring the use of the Old Testament in the New Testament (intertextuality). This study explores how a reimagining of the Old Testament mission can strengthen reconciliation and promote intercultural dialogue within the context of multicultural ecclesia. The analysis will also focus on the social impact of this renewing mission, including its effects on social relationships within and outside the ecclesia. The research findings provide insights that the renewing mission rooted in the teachings of the Old Testament, particularly in the interpretation and adaptation of the narrative of Acts 15, plays a significant role in facilitating reconciliation and positively influencing social dynamics within the context of multicultural ecclesia. Acts 15 offers inspiration and strong guidance for modern churches striving to integrate reconciliation, renewing mission, and social influence within the context of multicultural ecclesia. It reflects a genuine call to embody the mission of Christ, bringing transformation, and becoming living witnesses to reconciliation in a world full of diversity.Penelitian ini bertujuan untuk menyelidiki peran pembaruan misi berbasis Perjanjian Lama dalam proses rekonsiliasi di dalam konteks ekklesia multikultural. Fokus utama penelitian ini adalah pada naratif Kisah Para Rasul 15, yang memberikan kerangka kerja untuk memahami bagaimana pembaruan misi Perjanjian Lama dapat diadaptasi untuk mencapai rekonsiliasi di antara komunitas-komunitas beragam. penulis akan menggunakan pendekatan studi kepustakaan dalam literatur penggunaan Perjanjian Lama dalam Perjanjian Baru (intertekstual). Penelitian ini mengeksplorasi bagaimana pemahaman ulang terhadap misi Perjanjian Lama dapat memperkukuh rekonsiliasi dan mempromosikan dialog antarbudaya dalam konteks ekklesia multikultural. Analisis juga akan difokuskan pada pengaruh sosial dari pembaruan misi tersebut, termasuk dampaknya terhadap hubungan sosial di dalam dan di luar ekklesia. Hasil penelitian memberikan wawasan pembaruan misi yang bersumber dari ajaran Perjanjian Lama, khususnya dalam interpretasi dan adaptasi naratif Kisah Para Rasul 15, memiliki peran signifikan dalam memfasilitasi rekonsiliasi dan mempengaruhi positif dinamika sosial dalam konteks ekklesia multikultural. Kisah Para Rasul 15 memberikan inspirasi dan panduan yang kuat bagi gereja-gereja modern yang berjuang untuk mengintegrasikan rekonsiliasi, pembaruan misi, dan pengaruh sosial dalam konteks ekklesia multikultural. Ini adalah cerminan nyata dari panggilan untuk menjalani misi Kristus, membawa transformasi, dan menjadi saksi-saksi hidup rekonsiliasi dalam dunia yang penuh dengan keragaman.